Pollination facilitation and temporal changes of plant-floral visitor network in a serpentine shrubwood of Cuba - Alameda, Diego; Martínez Adriano, Cristian Adrián; Barro Cañamero, Alejandro (Journal of Pollination Ecology, 2025)
The stress-gradient hypothesis predicts that in stressful ecosystems, species interactions are facilitative rather than competitive. In Cuba, one of the more stressful environments for plants is serpentinitic shrubwoods (cuabales), which experience intense variations in precipitation and temperature. Plant facilitative mechanisms are reported in this ecosystem, and pollination facilitation could also occur. We hypothesize that in this seasonal ecosystem, characterized by harsh conditions, facilitative pollination interactions prevail accompanied by intense interaction rewiring and species turnover. This research analyzed the temporal variation of the plant-pollinator network of serpentinitic shrubwood in Lomas de Galindo, Mayabeque, Cuba. Data were obtained by monitoring diurnal plant-pollinator interactions for two days each month through one year. The network was composed of 31 plant species and 81 pollinator species, where ten modules of interactions were detected in the network. Nine species were identified as core species; four of them were plants that gathered the majority of interactions. However, plant core species change temporally. The changes in beta-diversity values were higher between the initial and final months of every season, which could be caused by the variations in phenology and changes in pollinators’ abundances. Facilitation occurred in six plant species that temporally segregate the pollination interactions and shaped the support of pollination in the community. For this reason, the conservation of pollination services in this ecosystem should be focused on these species.